Effect of dietary Halquinol supplementation on the productive performances, carcass traits and blood profile of Sonali chicken - Habib, Md Ahsan; Haque, Md Anowarul; Islam, Md Saiful; Liton, Md Ruknuzzaman (Asian Journal of Medical and Biological Research, 2020)
This study was conducted to evaluate the efficacy of dietary supplementation of Halquinol on productive performances, carcass characteristics and hematological parameters of Sonali chicken. A total number of 72 Sonali chicks of 07 days old were divided randomly into 04 experimental groups occupying 03 replications in each groups among which four dietary groups were considered i.e. control group (T0), Halquinol @ 0.25g/ kg feed in group (T1); Halquinol @ 0.5g/ kg feed in group (T2); and Halquinol @ 1g/ kg feed in group (T3) respectively. Results indicated that body weight and body weight gain were increased significantly (P<0.05) in birds supplied with Halquinol @ 1g/ kg feed group (T3) compared to the other groups. Higher (P<0.05) feed intake and better (P<0.05) FE were also observed in group T3 compared to the other groups. This result also indicated that body weight, body weight gain, feed intake, and feed efficiency were increased along with increasing dose of Halquinol. No significant (P>0.05) differences were found in dressing percentage, liver, heart and gizzard among the dietary treatment groups. However, the dressing weight, breast meat, thigh meat, and head weight was significantly (p<0.05) higher in birds supplied with Halquinol @ 1g/ kg feed group (T3) compare to control (T0) group. Present study revealed that hematological parameters, including Hb, PCV and ESR value of the birds of different groups does not differ significantly among the groups and it was within the normal range. Cost effective analysis of the experiment demonstrated that by using Halquinol @ 1g/ kg feed significantly (P<0.05) higher net profit than other dietary treatment groups and also highest profit over control (14.95Tk.). Based on the results of present study it may be suggested that supplementation of Halquinol can be used as a commercial growth promoter for the production of Sonali chicken. Asian J. Med. Biol. Res. June 2019, 5(4): 316-323